Impact of demographic characteristics of procurement professionals on sustainable procurement practices: Evidence from Australia. Issue 1 (March 2016) - Mansi, Mansi; Pandey, Rakesh
Abstract: The purpose of this study is to explore the impact of the demographic characteristics of procurement professionals on sustainable procurement (SP) practices inside Australian universities. The study addresses the "who" question—that is, who inside an organisation might be the most likely to engage in SP practices. Using a valuable sample of 224 procurement professionals, the findings of this study provide evidence that demographic characteristics such as working tenure, qualification and position predict SP practices, particularly in the areas of environment, philanthropy and safety. The study implies that if there are more qualified female procurement professionals, it is likely that an organisation will pursue environmentally friendly procurement activities. This is the first study to confirm the effect of the demographic characteristics of procurement professionals on SP dimensions, which to date has been completely undisclosed in the literature. It adds another dimension to understanding SP in the workplace. Highlights: Demographic characteristics impact SP practices. Male and female procurement professionals differ in their responses and women are more inclined towards environmentally friendly activities. Working tenure of procurement professionals can be seen as a measurement of his or her awareness or knowledge of SP practices. Position negatively affects the environment and philanthropy dimensions of SP practices. Qualified procurement professionals are more active in purchasing recycled packaging, and setting waste-reduction goals .